Reference intervals for insulin-like growth factor-1 (igf-i) from birth to senescence: results from a multicenter study using a new automated chemiluminescence IGF-I immunoassay conforming to recent international recommendations - Bidlingmaier, Martin; Friedrich, Nele; Emeny, Rebecca T; Spranger, Joachim; Wolthers, Ole D; Roswall, Josefine; Körner, Antje; Obermayer-Pietsch, Barbara; Hübener, Christoph; Dahlgren, Jovanna; Frystyk, Jan; Pfeiffer, Andreas F H; et al. (The journal of clinical endocrinology and metabolism, 2014)
Measurement of IGF-I is a cornerstone in diagnosis and monitoring of GH-related diseases, but considerable discrepancies exist between analytical methods. A recent consensus conference defined criteria for validation of IGF-I assays and for establishment of normative data. Our objectives were development and validation of a novel automated IGF-I immunoassay (iSYS; Immunodiagnostic Systems) according to international guidelines and establishment of method-specific age- and sex-adjusted reference intervals and analysis of their robustness. We conducted a multicenter study with samples from 12 cohorts from the United States, Canada, and Europe including 15 014 subjects (6697 males and 8317 females, 0-94 years of age). We measured concentrations of IGF-I as determined by the IDS iSYS IGF-I assay. A new IGF-I assay calibrated against the recommended standard (02/254) and insensitive to the 6 high-affinity IGF binding proteins was developed and rigorously validated. Age- and sex-adjusted reference intervals derived from a uniquely large cohort reflect the age-related pattern of IGF-I secretion: a decline immediately after birth followed by an increase until a pubertal peak (at 15 years of age). Later in life, values decrease continuously. The impact of gender is small, although across the lifespan, women have lower mean IGF-I concentrations. Geographical region, sampling setting (community or hospital based), and rigor of exclusion criteria in our large cohort did not affect the reference intervals. Using large cohorts of well-characterized subjects from different centers allowed construction of robust reference ranges for a new automated IGF-I assay. The strict adherence to recent consensus criteria for IGF-I assays might facilitate clinical application of the results.